A method for preparing implant material
By preparing high binding strength hydroxyapatite and calcium phosphate film layers on the surface of zirconia ceramics, the problem of low bond strength of adhesion materials on the surface of zirconia ceramics is solved, and the high biological activity and stability of implant materials are achieved. It is suitable for Dental implant.
Patent Information
- Application Number
- CN202210357651.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-06
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-04-06
AI Technical Summary
The binding strength of hydroxyapatite and/or calcium phosphate attached to the surface of zirconia ceramics is low, which affects the biological activity of binding to the human body, especially in dental implant materials.
By preparing the matrix slurry, pre-sintering is performed after drying to form a primary matrix, and then the first film blank is prepared on the surface and final sintering is performed to ensure that the inner matrix of the implant material is firmly combined with the membrane layer on the surface. The hydrothermal method is used to the primary matrix on the primary matrix Film formation is carried out on the surface to improve binding strength and biological activity.
The firm combination of the inner matrix and surface of the implant material is achieved, avoiding falling off and does not affect biological activity, and provides high-density and high-biological activity implant material, suitable for dental replacement materials.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a biomaterial, and in particular to the technical field of implant material preparation. Background Art
[0002] Biomaterials are materials that have the ability to repair, replace and regenerate body tissues; bioceramic materials have been widely developed and have broad prospects for use.
[0003] Bioceramic materials are divided into bio-inert ceramic materials and bio-active ceramic materials. Zirconia bioceramics belong to bio-inert ceramic materials, which have excellent wear resistance and mechanical strength and are generally used as tooth repair or replacement materials. Hydroxyapatite (HA) and tricalcium phosphate (TCP) bioceramics belong to bio-active ceramics. The structures of hydroxyapatite (HA) and tricalcium phosphate (TCP) are similar to biological bones, especially hydroxyapatite (HA), which is often used as bone replacement or repair material.
[0004] Therefore, the biomaterials using zirconium oxide ceramics combined with hydroxyapatite and / or tricalcium phosphate will have excellent wear resistance, mechanical strength and biological activity, which is beneficial to improving the biocompatibility of the biomaterial surface and better promoting the bone integration of the implant in the human body;
[0005] The problem is that the bonding strength of hydroxyapatite and / or calcium phosphate attached to the surface of zirconia ceramics is low, and delamination easily occurs, which affects the biological activity of the biomaterial in combination with the human body; how to prepare biomaterials with high bonding strength between hydroxyapatite and / or calcium phosphate and zirconia ceramic matrix, especially implant materials for replacing teeth, which have excellent biological activity and at the same time achieve high bonding strength between their internal matrix and the surface layer, is a technical difficulty in this field. Summary of the invention
[0006] In order to solve the problem of high bonding strength between the matrix inside the implant material and the surface layer, a method for preparing an implant material is provided, comprising the following steps: preparing a matrix slurry, and preparing the matrix slurry into a matrix blank; drying the matrix blank, and pre-sintering the matrix blank after drying to obtain a primary matrix; preparing a first film blank on the surface of the primary matrix, and then final sintering the primary matrix blank; the implant matrix inside the implant material finally obtained is firmly bonded to the film layer on the surface, and is not prone to falling off or damage during use, and the implant has high biological activity.
[0007] According to the present invention, a method for preparing an implant material is provided, wherein the preparation raw materials include the following steps: preparing a matrix slurry, preparing the matrix slurry into a matrix blank; drying the matrix blank, and pre-sintering the matrix blank after drying to obtain a primary matrix; preparing a first film blank on the surface of the primary matrix, and then final sintering the primary matrix blank to obtain the implant material; the obtained implant material includes an implant matrix and a first film layer coated on the surface of the implant matrix, and the density of the implant matrix is 5.7-6.0 g / cm 3 ; The porosity of the first film layer is greater than the porosity of the implant matrix.
[0008] The beneficial effect of the present invention over the prior art is that the primary matrix is obtained by drying the matrix blank and pre-sintering it after drying. The obtained primary matrix has a certain strength, and a variety of methods can be used to form a film on the surface of the primary matrix, especially a hydrothermal method can be used to form a film on the surface of the matrix; at the same time, the surface of the primary matrix is not completely sintered and has more voids and higher activity, which is beneficial to the bonding of part of the material of the first film blank with part of the material on the surface of the primary matrix during the final sintering after the first film blank is prepared on the surface of the primary matrix, so that the implant matrix inside the obtained implant material and the first film layer on the surface have high bonding strength and will not fall off; and the biological activity of the matrix and the surface layer is not affected; the density of the implant matrix is 5.7-6.0g / cm 3 , so that the implant material has sufficient strength and can improve biological activity at the same time; the porosity of the first film layer is greater than the porosity of the implant matrix, which is more conducive to achieving higher biological activity of the implant material.
[0009] Furthermore, the step of preparing the matrix slurry is as follows: solid powder, photocurable resin system solution and additives are mixed in proportion; the mass ratio of the solid powder, photocurable resin system solution and additives is (40-60): (30-55): (0.4-10);
[0010] The solid powder includes ZrO2 powder;
[0011] The photocurable resin system solution includes polymerizable monomers, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate;
[0012] The mass ratio of the polymerizable monomer, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate in the curing resin system solution is (45-55): (25-35): (15-20);
[0013] The polymerizable monomer is one or more of low-viscosity polyurethane acrylate, dipropylene glycol acrylate, tripropylene glycol diacrylate, bisphenol A epoxy acrylate, and hydroxyethyl methacrylate; the additives include a photoinitiator, a dispersant, and a leveling agent;
[0014] The photoinitiator is one or more of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-phenylacetone-1, and phenylphosphine oxide; the dispersant is one or more of Span-80, phosphate ester, and Triton X-114; preferably, the ZrO2 powder is 3% Y2O3 stabilized ZrO2; the particle size of the ZrO2 powder is 0.4-0.7μm; the viscosity of the matrix slurry is 4.5-5.8Pa·s (50s -1 );
[0015] The beneficial effect of adopting the above technical solution is that the mass ratio of the solid powder, the photocurable resin system solution and the additive is (40-60): (30-55): (0.4-10), which is conducive to obtaining a matrix blank with a high solid content, and is conducive to obtaining a high strength of the implant material, and is also conducive to the implant material having a suitable porosity, thereby improving the biological activity; the polymerized monomer is conducive to achieving a certain strength of the matrix blank, and is also conducive to achieving the polymer resin debinding after the monomers in the matrix blank are polymerized, so that the matrix blank does not crack or deform and the increase of the macropore volume is avoided; the photoinitiator is conducive to achieving a suitable strength of the matrix blank;
[0016] The ZrO2 powder is 3% Y2O3 stabilized ZrO2, and the particle size of the ZrO2 powder is 0.4-0.7 μm, which is beneficial to reducing the final sintering temperature.
[0017] Furthermore, during the drying process of the matrix blank, the drying temperature is 60-80° C. and the drying time is 12-20 hours; after drying, the moisture content of the matrix blank is 8-12%.
[0018] The beneficial effect of adopting the technical solution in the previous step is that it is conducive to debinding the matrix blank and to maintaining a certain moisture content in the matrix blank before pre-sintering, thereby ensuring that the primary matrix has sufficient strength and that the surface material of the primary matrix has a certain activity, which is conducive to bonding with the material in the first step membrane blank during the final sintering.
[0019] Furthermore, during the pre-sintering process, the pre-sintering temperature is 900-1100° C., the heating rate is controlled at 0.5-1.5° C. / min, and the holding time is 1-2 h.
[0020] The beneficial effect of adopting the above technical solution is that it is conducive to achieving sufficient strength of the primary matrix and maintaining a certain activity of the surface material of the primary matrix, which is conducive to bonding with the material in the first step membrane blank during final sintering.
[0021] Furthermore, the specific steps of preparing the first film blank on the surface of the primary blank are:
[0022] Prepare solution A and solution B; place the primary matrix in solution B, then drop solution A into solution B, and perform staged reactions during the dropping process, wherein the reaction temperature of the first stage is 58-62°C, and the reaction time of the first stage is 58-62min; the reaction temperature of the second stage is 88-92°C, and the reaction time of the second stage is 118-122min; the reaction temperature of the third stage is 150°C-180°C, and the reaction time of the third stage is 298-302min, and the reaction pressure of the third stage is 2-3MPa; then wash and dry.
[0023] The beneficial effect of adopting the previous technical solution is that by controlling the temperature in stages, the temperature is slowly increased in the first stage, and the effective contact of the reactants is gradually controlled to initially precipitate HA nuclei on the surface of the primary matrix; after the temperature is increased in the second stage, the reaction rate is accelerated, and the hydroxyapatite fully reacts under the temperature conditions to generate an HA coating on the surface of the primary matrix; the third reaction stage belongs to the hydrothermal stage, and HA is better in contact and adhesion to the primary matrix under high temperature and high pressure conditions, thereby improving the adhesion activity; finally, the first film blank is attached to the surface of the matrix blank, and the first film blank includes HA, and the HA is evenly attached and has high strength, and the implant material obtained after sintering includes a zirconia implant matrix and an HA film layer on the attachment surface, and the HA film layer has a high porosity, which is beneficial to further increase the biological activity of the implant material.
[0024] Furthermore, in the final sintering process, the final sintering temperature is 1350-1450° C., and the sintering time is 118-122 min.
[0025] The beneficial effect of adopting the above technical solution is that it can not only realize the sintering of the primary matrix and the first film blank, but also reduce the decomposition rate of HA in the first film blank, which is beneficial to improving the biological activity of the implant material.
[0026] Furthermore, the solution A comprises calcium ions and zinc ions, and the molar ratio of the calcium ions to the zinc ions is 0.01-0.05; the solution B comprises hydroxide ions, sodium dihydrogen phosphate and EDTA; and / or the molar ratio of the calcium element in the solution A to the phosphorus element in the solution B is 1.7-1.8.
[0027] The beneficial effect of adopting the previous technical solution is that the first film layer attached to the surface of the primary substrate includes HA; the molar ratio of the calcium element in the A solution to the phosphorus element in the B solution is 1.7-1.8, which avoids the loss of part of the Ca element or the inability to effectively enter the HA during the final sintering when the molar ratio of the calcium element in the A solution to the phosphorus element in the B solution is less than 1.7, thereby improving the stability of HA during the final sintering and the subsequent use of the finished product. When the molar ratio is too high, it is easy to cause the pores of the HA film layer on the surface of the implant to be too large, thereby reducing the strength and biological activity.
[0028] Furthermore, after the matrix slurry is prepared into a matrix blank, before the matrix blank is dried, an intermediate material layer is attached to the surface of the matrix blank; the specific process is as follows: intermediate material layer slurry is prepared, and the intermediate material layer slurry is coated on the surface of the primary blank; preferably, the density of the primary matrix is 4.0-5.0g / cm 3 The primary base body is finally sintered to obtain an implant material including an implant matrix and a first film layer, and an intermediate layer connecting the implant matrix and the first film layer; the density of the implant matrix is 5.7-6.0g / cm 3 .
[0029] The beneficial effect of adopting the previous technical solution is that the intermediate material layer attached to the surface of the substrate blank is conducive to improving the connection strength between the primary substrate and the first film layer after final sintering. At the same time, the intermediate material layer is conducive to reducing the decomposition rate of HA of the first film blank during the final sintering process, thereby improving the biological activity of the final implant material.
[0030] Furthermore, the intermediate layer slurry includes epoxy resin, cross-linking agent, zirconium oxide powder, and B2O3 powder;
[0031] The B2O3 powder accounts for 2%-8% of the total mass of the intermediate layer slurry; the viscosity of the intermediate layer slurry is 6-8Pa·s (50s -1 );
[0032] And / or the solid content of the intermediate layer slurry is 35-40%.
[0033] The beneficial effect of adopting the above technical solution is that the intermediate material layer slurry includes zirconium oxide powder, which is conducive to bonding the intermediate material layer with the surface of the primary substrate after final sintering, and the bonding strength is high; at the same time, the intermediate material layer slurry includes B2O3 powder, which is conducive to bonding the intermediate material layer with the first film blank after final sintering, and is conducive to achieving a firm bond between the intermediate material layer and the first film blank after final sintering, and is conducive to reducing the decomposition rate of HA in the first film blank during the final sintering process, thereby significantly improving the biological activity of the implant material;
[0034] The solid content of the intermediate material layer slurry is 35-40%, which is beneficial for the intermediate material layer to have a certain strength and activity after pre-sintering, which is beneficial for bonding reaction with the first membrane blank during final sintering, increasing the connection strength while reducing the decomposition rate of HA in the first membrane blank.
[0035] Furthermore, it is characterized in that the solid content of the intermediate layer slurry is less than the solid content of the base slurry.
[0036] The beneficial effect of adopting the previous technical solution is that it is conducive to achieving a certain strength and activity of the intermediate material layer after pre-sintering, which is conducive to bonding reaction with the first membrane blank during final sintering, increasing the connection strength while reducing the decomposition rate of HA in the first membrane blank. DETAILED DESCRIPTION
[0037] In order to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments.
[0038] Embodiment 1:
[0039] The present embodiment provides a method for preparing an implant material, wherein the preparation raw materials include the following steps: preparing a matrix slurry, preparing the matrix slurry into a matrix blank; drying the matrix blank, and pre-sintering the matrix blank after drying to obtain a primary matrix; preparing a first film blank on the surface of the primary matrix, and then final sintering the primary matrix blank to obtain the implant material; the obtained implant material includes an implant matrix and a first film layer coated on the surface of the implant matrix, and the density of the implant matrix is 5.8 g / cm 3 ; The porosity of the first film layer is greater than the porosity of the implant matrix.
[0040] The steps of preparing the matrix slurry are as follows: solid powder, photocurable resin system solution and additives are mixed in proportion; the mass ratio of the solid powder, photocurable resin system solution and additives is 50:43:7;
[0041] The solid powder includes ZrO2 powder; the ZrO2 powder is 3% Y2O3 stabilized ZrO2; the ZrO2 powder has a particle size of 0.55 μm;
[0042] The photocurable resin system solution includes polymerizable monomers, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate;
[0043] The mass ratio of the polymerizable monomer, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate in the curing resin system solution is 50:30:18;
[0044] The polymerizable monomers are low-viscosity polyurethane acrylate and dipropylene glycol acrylate; the additives include a photoinitiator, a dispersant and a leveling agent;
[0045] The photoinitiator is diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide; the dispersant is phosphate ester; the matrix slurry viscosity is 5.1 Pa·s (50s -1 );
[0046] During the drying process of the matrix green body, the drying temperature is 70° C. and the drying time is 18 hours; after drying, the moisture content of the matrix green body is 10%.
[0047] During the pre-sintering process, the pre-sintering temperature is 1000° C., the heating rate is controlled at 1.0° C. / min, and the holding time is 1.5 h.
[0048] The specific steps of preparing the first film blank on the surface of the primary blank are:
[0049] Prepare solution A and solution B; place the primary matrix in solution B, then drop solution A into solution B, and perform staged reactions during the dropping process, wherein the first stage reaction temperature is 60°C and the first stage reaction time is 60min; the second stage reaction temperature is 90°C and the second stage reaction time is 120min; the third stage reaction temperature is 165°C and the third stage reaction time is 300min, and the third stage reaction pressure is 2.5MPa; then wash and dry;
[0050] The solution A includes calcium ions and zinc ions, and the molar ratio of the calcium ions to the zinc ions is 0.03; the solution B includes hydroxide ions, sodium dihydrogen phosphate and EDTA; the molar ratio of the calcium element in the solution A to the phosphorus element in the solution B is 1.75.
[0051] In the final sintering process, the final sintering temperature is 1400° C. and the sintering time is 120 min.
[0052] Embodiment 2:
[0053] The contents of this embodiment that are the same as those of embodiment 1 are not repeated here; the density of the implant matrix is 5.9 g / cm 3 .
[0054] The mass ratio of the solid powder, the photocurable resin system solution and the additive is 58:38:4; the particle size of the ZrO2 powder is 0.6 μm;
[0055] The mass ratio of the polymerizable monomer, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate in the curing resin system solution is 46:34:20;
[0056] The polymerizable monomers are tripropylene glycol diacrylate and bisphenol A epoxy acrylate; the photoinitiator is 2-hydroxy-2-methyl-phenylacetone-1; the dispersant is Span-80; the matrix slurry viscosity is 5.5 Pa·s (50s -1 );
[0057] During the drying process of the matrix green body, the drying temperature is 65° C. and the drying time is 13 hours; after drying, the moisture content of the matrix green body is 9%.
[0058] During the pre-sintering process, the pre-sintering temperature is 950°C, the heating rate is controlled at 0.6°C / min, and the holding time is 1.2h;
[0059] The specific steps of preparing the first film blank on the surface of the primary blank are:
[0060] The solution A includes calcium ions and zinc ions, and the molar ratio of the calcium ions to the zinc ions is 0.02; the molar ratio of the calcium element in the solution A to the phosphorus element in the solution B is 1.71.
[0061] Embodiment 3:
[0062] The contents of this embodiment that are the same as those of embodiment 1 are not repeated here; after the base slurry is prepared into a base body, before the base body is dried, an intermediate material layer is attached to the surface of the base body;
[0063] The steps of preparing the matrix slurry are as follows: the mass ratio of the solid powder, the photocurable resin system solution and the additive is 43:55:2;
[0064] The ZrO2 powder has a particle size of 0.65 μm;
[0065] The mass ratio of the polymerizable monomer, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate in the curing resin system solution is 55:28:17;
[0066] The polymerization monomers are bisphenol A epoxy acrylate and hydroxyethyl methacrylate; the photoinitiator is phenyl phosphorus dioxide; the dispersant is Triton X-114; the matrix slurry viscosity is 4.4 Pa·s (50s -1 );
[0067] The specific process of attaching the intermediate material layer to the surface of the base body is as follows: prepare the intermediate material layer slurry, and coat the intermediate material layer slurry on the surface of the primary body; the density of the primary base body is 4.2g / cm 3 The primary base body is finally sintered to obtain an implant material including an implant matrix and a first film layer, and an intermediate layer connecting the implant matrix and the first film layer; the density of the implant matrix is 5.7g / cm3 .
[0068] The intermediate material layer slurry includes epoxy resin, cross-linking agent, zirconium oxide powder and B2O3 powder;
[0069] The B2O3 powder accounts for 5% of the total mass of the intermediate layer slurry; the viscosity of the intermediate layer slurry is 7Pa·s (50s -1 ); the solid content of the intermediate material layer slurry is 36%; the solid content of the intermediate material layer slurry is less than the solid content of the base slurry;
[0070] In the final sintering process, the final sintering temperature is 1430° C. and the sintering time is 121 min.
[0071] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features have similar functions to those disclosed in the present application (but not limited to).
Claims
1. A method for preparing an implant material, characterized in that: The following steps are involved: preparing a matrix slurry, and preparing the matrix slurry into a matrix green body; Drying the matrix green body, and pre-sintering after drying to obtain a primary matrix; After the matrix slurry is prepared into a matrix green body, before the matrix green body is dried, an intermediate material layer is attached to the surface of the matrix green body; the specific process is as follows: preparing the intermediate material layer slurry, and coating the surface of the primary green body with the intermediate material layer slurry; The intermediate material layer slurry includes epoxy resin, cross-linking agent, zirconium oxide powder and B2O3 powder; The B2O3 powder accounts for 2%-8% of the total mass of the intermediate layer slurry; the viscosity of the intermediate layer slurry is 6-8Pa•s / 50 s -1 ; The solid content of the intermediate layer slurry is 35-40%; During the drying process of the matrix body, the drying temperature is 60-80°C and the drying time is 12-20h; after drying, the moisture content of the matrix body is 8-12%; The first film blank is prepared on the surface of the primary substrate, and then the primary substrate is finally sintered to obtain the implant material comprising an implant substrate and a first film layer coated on the surface of the implant substrate, and the density of the implant substrate is 5.7-6.0 g / cm 3 ; The porosity of the first film layer is greater than the porosity of the implant matrix; During the pre-sintering process, the pre-sintering temperature is 900-1000 ℃, the heating rate is controlled at 0.5-1.5 ℃ / min, and the holding time is 1-2h; The specific steps of preparing the first film blank on the surface of the primary substrate are: Prepare solution A and solution B; The primary matrix is placed in solution B, and then solution A is added dropwise to solution B, and a stage reaction is performed during the dropping process, wherein the first stage reaction temperature is 58-62°C, and the first stage reaction time is 58-62 minutes; the second stage reaction temperature is 88-92°C, and the second stage reaction time is 118-122 minutes; the third stage reaction temperature is 150°C-180°C, and the third stage reaction time is 298-302 minutes; Then wash and dry; The A solution includes calcium ions and zinc ions, and the molar ratio of the calcium ions to the zinc ions is 0.01-0.05; The B solution includes hydroxide ions, sodium dihydrogen phosphate and EDTA; the steps of preparing the matrix slurry are as follows: solid powder, photocurable resin system solution and additives are mixed in proportion; the mass ratio of the solid powder, photocurable resin system solution and additives is (40-60): (30-55): (0.4-10); The solid powder includes ZrO2 powder; The photocurable resin system solution includes polymerizable monomers, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate; The mass ratio of the polymerizable monomer, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate in the curing resin system solution is (45-55): (25-35): (15-20); The polymerizable monomer is one or more of low-viscosity polyurethane acrylate, dipropylene glycol acrylate, tripropylene glycol diacrylate, bisphenol A epoxy acrylate, and hydroxyethyl methacrylate; The additives include photoinitiators, dispersants and leveling agents.
2. The method for preparing an implant material according to claim 1, characterized in that: The photoinitiator is one or more of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-phenylacetone-1, and phenylphosphine dioxide; The dispersant is one or more of Span-80, phosphate ester and Triton X-114.
3. The method for preparing an implant material according to claim 1, characterized in that: In the final sintering process, the final sintering temperature is 1350-1450° C., and the sintering time is 118-122 minutes.
4. The method for preparing an implant material according to claim 3, characterized in that: The molar ratio of the calcium element in the A solution to the phosphorus element in the B solution is 1.7-1.
8.
5. The method for preparing an implant material according to claim 1, characterized in that: The solid content of the intermediate layer slurry is less than the solid content of the base slurry.
Citation Information
Patent Citations
Slurry for photo-curing 3D-printing dental implant as well as preparation method and application of slurry
CN107158474A
Preparation method of biological ceramic surface coating medical implant
CN112430086A